Regioselective enzymatic synthesis of estradiol 17-fatty acid esters - Rustoy, E.M.; Ruiz Arias, I.E.; Baldessari, A.
A series of acyl esters of 3,17-β-estradiol has been prepared by an enzymatic methodology. Eleven 17-monoacyl products (five novel compounds) were obtained in a highly regioselective way by acylation of 3,17-β-estradiol or by alcoholysis of the corresponding diacyl derivatives. The influence of various reaction parameters such as molar ratio, enzyme:substrate ratio and temperature was evaluated. Among the tested lipases, Candida rugosa lipase appeared to be the most appropriate in monoacylation and lipase from Candida antarctica in alcoholysis. The advantages presented by this methodology such as mild reaction conditions, economy and low environmental impact, make the biocatalysis a convenient way to prepare monoacyl derivatives of 3,17-β-estradiol containing the aromatic 3-hydroxyl group free. Some of these compounds are recongnized as useful products in the pharmaceutical industry. ©ARKAT. Fil:Rustoy, E.M. Universidad de Buenos Aires. Facultad de Ciencias Exactas y Naturales; Argentina. Fil:Baldessari, A. Universidad de Buenos Aires. Facultad de Ciencias Exactas y Naturales; Argentina.